Association between serum ferritin level and the various stages of non-alcoholic fatty liver disease: A systematic review - Wang, Huanqiu; Sun, Ruyu; Yang, Sisi; Ma, Xueqing; Yu, Chengbo (Frontiers in Medicine, 2022)
Introduction: Non-alcoholic fatty liver disease (NAFLD) has become the most common liver disorder across the world, and non-invasive evaluation approaches are in need to assess NAFLD disease progression. Serum ferritin has been proposed as one of the biomarkers for NAFLD diagnosis in previous studies. This systematic review aims to identify, report, and synthesize studies that investigated the association of serum ferritin level with the various stages of NAFLD among the adult population. Methods: Three databases – MEDLINE, EMBASE, and Scopus – were systematically searched to obtain potentially relevant publications before July 2022. No restrictions were applied to geographical region, study design, publication type and language. The association between serum ferritin level or different ferritin categories and the various stages of NAFLD was the primary outcome of interest. Title and abstract screenings, data extraction and coding, and quality assessment were independently completed by two authors with discrepancies resolved through discussion with a third author. Results: Thirty-two studies were included and heterogeneity was considerable. The associations between serum ferritin level and the stages of hepatic steatosis, fibrosis, inflammation and ballooning and the occurrence of non-alcoholic steatohepatitis (NASH) were investigated but inconsistent associations were reported. Most studies identified serum ferritin to be a predictor of advanced NAFLD, while several revealed the opposite end. Conclusions: Serum ferritin could be considered to act as a non-invasive biomarker for assessing various stages of NAFLD. Nevertheless, further studies are still in need to confirm its predictive value since this study reported inconsistent associations based on the qualitative synthesis.